Harvesting The Results and Impact of Research based on Historical Longitudinal Databases - Edvinsson, Sören; Mandemakers, Kees; Smith, Ken Robert; Puschmann, Paul (Radboud University Press, 2023)
This edited volume discusses the impact of several major databases containing historical longitudinal population data. The creation and development of these databases have greatly expanded research possibilities in history, demography, sociology, and other disciplines. The present collection includes seven contributions, on eight databases, that had a wide impact on research in various disciplines. Each database had its own unique genesis and readers are informed about how these databases have changed the course of research in historical demography and related disciplines, how settled findings were challenged or confirmed, and how innovative investigations were launched and implemented. The volume serves as an essential resource for scholars in the field of historical life course studies, offering insights into the transformative power of these databases and their potential for future advancements.